STUDENTS' MATHEMATICAL LITERACY IN SOLVING HIGHER ORDER THINKING SKILL PROBLEMS ON MATRIX MATERIAL - Yanti, Ili; Asiani, Rosi Widia; Kukuh, Muhammad (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
This qualitative descriptive study aims to describe students' mathematical literacy skills in solving Higher Order Thinking Skills (HOTS) questions on matrix material. The method used in this research is qualitative method. The subjects of this study were 6 students of class XI IPA SMA Al-Azhar Jambi. The instrument used is the initial ability test which contains 5 items, the Higher Order Thinking Skills (HOTS) written test which contains 3 essay questions and interview guidelines. Data analysis techniques include domain, taxonomy and componential analysis. The results of this study are: 1) It shows that all subjects meet the communication indicators (except S6), S1, S2, S3, S4 almost meet the indicators of mathematization, problem solving strategies and the use of formal and symbolic language, technical and operational languages, S5 and S6 do not meet the three indicators, and 2) the factors that affect mathematical literacy skills are: students' perceptions of the importance of mathematics, self-confidence in mathematical abilities, teacher quality in teaching, teacher character in teaching, models, media, strategies, approaches used in teaching, learning, limited time in working, level of HOTS questions and student interest in solving problems.